EGFR-Mutant Lung Adenocarcinoma Mimicking a Pneumonia - Álvaro Taus; Flavio Zuccarino; Carlos Trampal; Edurne Arriola (Case Reports in Pulmonology)
PET-CT scan has demonstrated to be very effective in lung cancer diagnosis and staging, but lung cancer has multiple ways of presentation, which can lead to an error in diagnosis imaging and a delay on the beginning of specific treatment. We present a case of a 77-year-old man with an initial PET-CT scan showing high 18F-FDG intake, suggesting a bilateral pneumonia, who was finally diagnosed of an EGFR-mutant lung adenocarcinoma. EGFR-activating mutation allowed us to start treatment with the oral tyrosin kinase inhibitor Gefitinib, obtaining a rapid and sustained response. Histological confirmation of imaging findings is always necessary to avoid diagnostic errors.